Inter rupting Chicken - Stein, David Ezra. (Somerville, Massachusett : Candlewick Press, 2010)
Little Red Chicken wants Papa to read her a bedtime story, but interrupts him almost as soon as he begins each tale.
K-3.
K-3
Keywords: Chickens -- Fiction; Humorous stories; Bedtime -- Fiction; Storytelling -- Fiction